Age-Dependent Metabolomic Profile of the Follicular Fluids From Women Undergoing Assisted Reproductive Technology Treatment - Huang, Yun; Tu, Mixue; Qian, Yuli; Ma, Junyan; Chen, Lifen; Liu, Yifeng; Wu, Yiqing; Chen, Kai; Liu, Juan; Ying, Yanyun; Chen, Yao; Ye, Yinghui; et al. (Frontiers in Endocrinology, 2022)
Female fertility declines with age, and this natural variation culminates in reproductive senescence. Human follicular fluids are rich in low-molecular weight metabolites which are responsible for the maturation of oocytes. The metabolomic approaches are powerful tools to study biochemical markers of oocyte quality in the follicular fluids. It is necessary to identify and quantify the reliable metabolites in follicular fluids reflecting oocyte developmental potential. The goal of this study is to conduct a metabolomic analysis of the follicular fluids in women of different ages and study the metabolomic profile of the follicular fluids in relationship with oocyte quality in assisted reproductive technology (ART) treatment. A total of 30 women seeking for ART treatment at the Women's Hospital, Zhejiang University School of Medicine from October 2014 to April 2015 were recruited for the present study. Fifteen women aged from 39 to 47 were grouped as advanced maternal age, and the other 15 women aged from 27 to 34, as young controls. Ovarian stimulation and oocyte retrieval were conducted using a regular protocol involving mid-luteal pituitary down-regulation and controlled ovarian stimulation. Follicular fluids from mature follicles were collected and centrifuged for analyses. Liquid Chromatography-Mass Spectrometry (LC-MS) and Gas Chromatography-Mass Spectroscopy (GC-MS) were used to perform the targeted quantitative metabolomic analysis. The follicular fluid levels of 311 metabolites and the metabolic significance were assessed. 70 metabolites showed significant differences between women with young and advanced ages. Follicular fluids from women with advanced age showed significantly higher levels of creatine, histidine, methionine, trans-4-hydroxyproline, choline, mevalonate, N2,N2-dimethylguanosine and gamma-glutamylvaline, as compared to those from the young age group. 8 metabolites were found significantly correlated with maternal age positively. Moreover, 3 metabolites were correlated with the number of oocytes retrieved, and 5 metabolites were correlated with cleaved embryo numbers, both negatively. The follicular fluids from women undergoing ART treatment exhibited age-dependent metabolomic profile. Metabolites associated with oocyte quality were identified, suggesting them as potential biomarkers for oocyte maturation and ART outcomes.